LA SAGA DE CEDRÓN LA ESCRITURA DE LA DECADENCIA DEL ORDEN COMUNAL - Vega Bedoya, Wilfrido Esteban (Cuadernos de Literatura del Caribe e Hispanoamérica, 2005)
En este ensayo se muestra cómo en la narrativa de Héctor Rojas Herazo se consolida una escritura neobarroca configurada en una expresión del desencanto frente a la degradación del orden comunal y en una escritura crítica que da cuenta de la desilusión por la deformación y conversión de la inocencia creativa y sensorial de la infancia en crudeza, horror y desamor. PALABRAS CLAVES Escritura, neobarroco, degradación, orden comunal, inocencia. ABSTRACT The topic on this essay is the new baroque writing of Hector Rojas Herazo. The central thesis is: The poetry of his novels is built upon the two dimensions of the text –content and form–. On the first one, we can see a disenchantment’s expression against the degradation of the communal organization; on the second one, it is the critical writing of the disillusionment that produces on the soul the transformation of the creative innocence and sensitive children’s spirit into harshness, horror and loveless. KEY WORDS Writing, new baroque, degradation, communal organization, innocence.